Response category width as a psychophysical manifestation of construal level and distance: $hTobias Krüger, Klaus Fiedler, Alex Stefan Koch, and Hans Alves - Krüger, Tobias; Fiedler, Klaus; Koch, Alex Stefan; Alves, Hans (Personality and social psychology bulletin, 2014)
The present research suggests that people adjust their mental response scales to an object’s distance and construal level. People make use of wider response categories when they judge distant and abstract as compared with close and concrete stimuli. Across five experiments, participants worked on visual and verbal estimation problems (e.g., length or quantity judgments). Answers were provided in interval format, and differences between minimal and maximal estimates served as a measure of response category width.
First published December 18, 2013
Gesehen am 22.09.2020